Kinerja Lajnah Pentashihan Mushaf Al-Qur'an: Studi Kasus Bidang Pentashihan Mushaf Al-Qur'an dengan Menggunakan Teori Urgency, Seriousness, Growth (USG) - Enang Sudrajat (SUHUF, 2008)
This writing is a research on the work-ethos (the work ethics) of the Institute of the Correction for the Qur'anic Manuscript (Lajnah Pentashihan Mushaf Al-Qur'an), the institute of research, development, education and training of the Ministry of Religious Affairs of the Republic of Indonesia by using the theory of USG (Urgency, Seriousness, Growth). It is from the description and explanation as well as observation, the writer concludes that (1) the level of work ethics service of the correction for the Qur'anic manuscript is still low and is needed to be improved, and (2) for certain skills such as the knowledge about the art of writing the manuscript (rasm Al-Qur'an) is also needed to be improved The strategy worth doing is to improve its human resources by conducting workshop, trainings, managing the work room and monitoring all the activities either to the publisher of the Qur'an or to society.